Experimental study on the storage performance of the innovative spray-type packed bed thermal energy storage. (25th January 2023) - Lin, Lin; Wang, Liang; Bai, Yakai; Lin, Xipeng; Zhang, Shuang; Ge, Zhiwei; Peng, Long; Chen, Haisheng
Highlights: A 10 kW spray-type packed bed thermal energy storage test rig was built. Effect of charging temperature, flow rate and cut-off temperature were discussed. Charge and discharge behavior of thermal energy under different states were studied. Energy and exergy efficiency achieved 96.06 % and 54.29 % over 5 cycles. Abstract: Thermal energy storage (TES) has been recognised as an effective way to overcome the temporal mismatch between energy generation and users' requirements. The innovative spray-type packed bed TES technology has promising development prospects owing to its advantages of high efficiency and low cost. In this study, a 10 kW/10 kWh spray-type packed bed TES test rig with aluminium spheres as storage media and thermal oil as the heat transfer fluid was established. The effects of parameters, including the charging temperature, flow rate, and cut-off temperature, as well as continuous-cycle experiments, on the heat storage performance were investigated. The experimental results show that the charging temperature and flow rate had little effect on the thermocline. A more even radial temperature distribution was obtained at a higher charging temperature and lower flow rate. The efficiency analysis indicated that increases in the values of the studied parameters promoted exergy efficiency, whereas only the flow rate was positive correlated with energy efficiency. Furthermore, energy efficiency was found to exceed 90 % in most cases in this study. During continuous cycles, the energy and exergy efficiencies can reach 96.06 % and 54.29 %, respectively.